Global Industrial Development: Insights From the Distribution Dynamics Approach for the Post Covid Era - Ma, Ning; Shum, Wai Yan; Han, Tingting; Cheong, Tsun Se (Frontiers in Public Health, 2021)
The spread of COVID-19 has significantly dampened global economic activity and has also wreaked havoc on the industrial sector. Industrial development plays an important role in national economic growth. Although industrialisation is not the only feasible way to attain the living standards of developed countries, it has been proven a potent force. In the past few decades, enormous efforts have been made in developing countries to pursue industrial development. Countries such as China, India, and South Korea have achieved success in alleviating income inequality and maintaining a good progress in industrial development. However, in many countries, severe underdevelopment and inequality still exist. Understanding the disparity and convergence of global industrial outputs is important in assessing the effectiveness of concurrent development policies. This study investigates the spatial distribution of global industrial output to unveil the disparity in industrial development and the feasibility of achieving convergence over time. Stochastic kernel analyses are carried out for national regimes to study the overall pattern of industrialisation for all the countries in the world. Countries are then classified into different groups to further analyse the geographical and income effects on industrial development.